Molecular Epidemiology and Antimicrobial Resistance of Clostridioides difficile in Hospitalized Patients From Mexico - Aguilar-Zamora, Emmanuel; Weimer, Bart C.; Torres, Roberto C.; Gómez-Delgado, Alejandro; Ortiz-Olvera, Nayeli; Aparicio-Ozores, Gerardo; Barbero-Becerra, Varenka J.; Torres, Javier; Camorlinga-Ponce, Margarita (Frontiers in Microbiology, 2022)
Molecular epidemiology and antimicrobial resistance in hospitalized patients from Mexico Emmanuel Aguilar-Zamora1,2, Bart C. Weimer6, Roberto C. Torres1, Alejandro Gómez- Delgado1, Nayeli Ortiz-Olvera3, Gerardo Aparicio-Ozores4, Varenka Barbero-Becerra5, Javier Torres1*, Margarita Camorlinga-Ponce1* Abstract. Clostridioides difficile is a global public health problem, which is a primary cause of antibiotic-associated diarrhea in humans. The emergence of hypervirulent and antibiotic resistant strains is associated with the increased incidence and severity of the disease. There are limited studies on genomic characterization of C. difficile in Latin America. We aimed to learn about the molecular epidemiology and antimicrobial resistance in C. difficile strains from adults and children in hospitals of México. We studied 94 C. difficile isolates from seven hospitals in Mexico City from 2014 to 2018. Whole-genome sequencing (WGS) was used to determine the genotype and examine the toxigenic profiles. Susceptibility to antibiotics was determined by E-test. Multilocus sequence typing (MLST) was used to determine allelic profiles. Results identified 20 different sequence type (ST) in the 94 isolates, mostly Clade-2 and Clade-1. ST1 was predominant in isolates from adult and children. Toxigenic strains comprised 87.2% of the isolates that were combinations of tcdAB and cdtAB (tcdA+/tcdB+/cdtA+/cdtB+, followed by tcdA+/tcdB+/cdtA-/cdtB-, tcdA-/tcdB+/cdtA-/cdtB-, and tcdA-/tcdB-/cdtA+/cdtB+). Toxin profiles were more diverse in isolates from children. All 94 isolates were susceptible to metronidazole and vancomycin, whereas a considerable number of isolates were resistant to clindamycin, fluroquinolones, rifampicin, meropenem, and linezolid. Multidrug resistant isolates (≥3 antibiotics) comprised 65% of the isolates. The correlation between resistant genotypes and phenotypes was evaluated by the Kappa test. Mutations in rpoB and rpoC showed moderate concordance with resistance to rifampicin and mutations in fusA substantial concordance with fusidic acid resistance. cfrE a gen recently described in one Mexican isolate, was present in 65% of strains linezolid resistant, all ST1 organisms. WGS is a powerful tool to genotype and characterize virulence and antibiotic susceptibility patterns. Running title: Genomic and phenotypic C. difficile epidemiology